A three-component reagent system for rapid and mild removal of O-, N- and S-trityl protecting groups - Kicsák Máté; Bege Miklós; Bakai-Bereczki Ilona; Csávás Magdolna; Herczeg Mihály; Kupihár Zoltán; Kovács Lajos; Borbás Anikó; Herczegh Pál (2016)
A new reagent system consisting of a Lewis acid such as BF3·Et2O or Cu(OTf)2, the mild protic acid hexafluoroisopropanol and the reducing quenching agent triethylsilane was elaborated for O-, N- and S-detritylation of nucleoside, carbohydrate and amino acid derivatives. The method is compatible with acetyl, silyl, acetal and Fmoc groups.
Keywords: Kémiai tudományok; Biológiai tudományok